Improving students’ mathematical reasoning through discovery learning - Peranginangin, Andreas P. (Indonesian Research Journal in Education |IRJE|, 2026)
This study examines the effect of the discovery learning model on students’ mathematical reasoning ability. The research employed a quasi-experimental design involving two eleventh-grade classes: an experimental group taught using discovery learning and a control group taught using conventional instruction. Data were collected through a mathematical reasoning test administered before and after the treatment. The results indicate that students in the experimental group demonstrated significantly greater improvements in mathematical reasoning than those in the control group. Statistical analysis showed that discovery learning had a positive, meaningful impact on students’ ability to analyze problems, construct logical arguments, and draw conclusions. These findings suggest that discovery learning provides a more effective learning environment for developing higher-order thinking skills in mathematics. Therefore, the model is recommended as an alternative instructional strategy to enhance students’ mathematical reasoning in secondary education.